PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 1 KAWO TAHUN AJARAN 2019/2020 - Teguh Adi Saputra; Nurul Kemala Dewi; Siti Istiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
This research aimed to find there is or there no The Effect of Problem Based Learning Model Toward Result of Studying Mathematics at The Fourth Grade Students of SDN 1 Kawo in Academic Years 2019/2020. This research is experimental research the kind of research is quasi-experimental type nonequivalent control group design. This population of the research consists of all the fourth grade of a student at SDN 1 Kawo. The sampling technique of this research used Purposive sampling with total sample nineteen students fourth grade A and seventeen students grade B at SDN 1 Kawo. The technique of data collecting of this research is the learning outcome tested multiple-choice test. (pre-test and post-test). To analyze data the researcher used SPSS 21 Version. Testing research Hypothesis used independent test calculation sample t-test. The result of data analysis showed the t-test was 2.551 and t-table was 2.028 the level of significance 5% with a degree of freedom 34 it could be concluded that Ha was accepted and Ho was rejected. The hypothesis of Research accepted read that on The Effect of Problem Based Learning Model Toward Result of Studying Mathematics At Fourth Grade Students of SDN 1 KAWO In Academic Years 2019/2020.